Conservation status of the world's skinks (Scincidae): Taxonomic and geographic patterns in extinction risk. (May 2021) - Chapple, David G.; Roll, Uri; Böhm, Monika; Aguilar, Rocío; Amey, Andrew P.; Austin, Chris C.; Baling, Marleen; Barley, Anthony J.; Bates, Michael F.; Bauer, Aaron M.; Blackburn, Daniel G.; Bowles, Phil; et al.
Abstract: Our knowledge of the conservation status of reptiles, the most diverse class of terrestrial vertebrates, has improved dramatically over the past decade, but still lags behind that of the other tetrapod groups. Here, we conduct the first comprehensive evaluation (~92% of the world's ~1714 described species) of the conservation status of skinks (Scincidae), a speciose reptile family with a worldwide distribution. Using International Union for Conservation of Nature (IUCN) criteria, we report that ~20% of species are threatened with extinction, and nine species are Extinct or Extinct in the Wild. The highest levels of threat are evident in Madagascar and the Neotropics, and in the subfamilies Mabuyinae, Eugongylinae and Scincinae. The vast majority of threatened skink species were listed based primarily on their small geographic ranges (Criterion B, 83%; Criterion D2, 13%). Although the population trend of 42% of species was stable, 14% have declining populations. The key threats to skinks are habitat loss due to agriculture, invasive species, and biological resource use (e.g., hunting, timber harvesting). The distributions of 61% of species do not overlap with protected areas. Despite our improved knowledge of the conservation status of the world's skinks, 8% of species remain to be assessed, and 14% are listed as Data Deficient. The conservation status of almost a quarter of the world's skink species thus remains unknown. We use our updated knowledge of the conservation status of the group to develop and outline the priorities for the conservation assessment and management of the world's skink species. Highlights: 20% of skink species are threatened with extinction, and nine species are extinct. Key threats to skinks are agriculture, invasive species and biological resource use. Most species listed under IUCN Red List Criterion B Taxonomic and geographic biases in extinction risk are evident in skinks. 8% of skink species remain unassessed, and 14% are listed as Data Deficient.